Diffusion Barriers Block Defect Occupation on Reduced CeO2 (111) - Lustemberg, Pablo German (2016)
Surface defects are believed to govern the adsorption behavior of reducible oxides. We challenge this perception on the basis of a combined scanning-tunneling-microscopy and density-functional-theory study, addressing the Au adsorption on reduced CeO2-x(111). Despite a clear thermodynamic preference for oxygen vacancies, individual Au atoms were found to bind mostly to regular surface sites. Even at an elevated temperature, aggregation at step edges and not decoration of defects turned out to be the main consequence of adatom diffusion. Our findings are explained with the polaronic nature of the Au-ceria system, which imprints a strong diabatic character onto the diffusive motion of adatoms. Diabatic barriers are generally higher than those in the adiabatic regime, especially if the hopping step couples to an electron transfer into the ad-gold. As the population of O vacancies always requires a charge exchange, defect decoration by Au atoms becomes kinetically hindered. Our study demonstrates that polaronic effects determine not only electron transport in reducible oxides but also the adsorption characteristics and therewith the surface chemistry.